‘Vivek QPM 9’ maize: A hybrid for Himalayan hills and Peninsular region - Gupta, H S; Mahajan, Vinay; Agrawal, P K; Bisht, G S; Pant, M C (Indian Farming, 2015)
‘Vivek QPM 9’ is QPM version of the most successful single cross hybrid ‘Vivek Maize Hybrid 9’ developed through conversion of its parental lines through ‘marker assisted selection’ strategy complementrary to conventional hybrid breeding method. The grains of ‘Vivek QPM 9’ are yellow, semi-flint, flat and mediumbold with average 1,000 grain weight of 310 g. It matures in 85-90 days in hills and 80-85 days in plains. An average yield performance of ‘Vivek QPM 9’ was 58.43 q/ha and 54.35 q/ha in zone I and zone IV, respectively.